Penerapan Metode Integrasi Teileren-Poject pada Program Inovasi IPTEK dan Kreativitas Guru di SMKN 9 Kabupaten Garut dalam Kegiatan Workshop Mikrokontroler - Budi Herdiana; Muhammad Aria; Tri Rahajoeningroem; Bobi Kurniawan; Jana Utama; Budi Hartono (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2018)
Success of workshop activities in community programs can be seen from the results of these activities which are able to improve students' skills to implement their knowledge that had been obtained previously. This program was done at SMKN 9 aimed at providing innovation and enhancing the creativity of teachers' skills in the field of microcontroller systems. Therefore the ability to understand microcontroller system requires supporting facilities such as hardware and software devices than also require a comprehensive and systematic of learning process. The alternative solution to problem is done by collaborating teileren method and project method simultaneously where learning subject is focused on the workshop material step by step before applying it. The expectation from this program is that teachers can get used to and have the ability to design microcontroller systems that can be applied as teaching materials and curriculum development. The accomplishment of this workshop can be measured by pre-test evaluation which shows value >65% and post-test results which shows an average value of >70% with an average index of teacher capacity improvement based on final evaluation >60% compared to the previous test scores.